EFFECT OF CATALASE AND CULTURAL CONDITIONS ON GROWTH OF BEGGIATOA, - Burton, Sheril D. (1964)
Burton, Sheril D. (Oregon State University, Corvallis), and Richard Y. Morita. Effect of catalase and cultural conditions on growth of Beggiatoa. J. Bacteriol. 88:1755–1761. 1964.—The addition of catalase to culture medium increased the period of viability of Beggiatoa from 1 week to 2 months. Addition of catalase also produced a marked increase in cell yield and enzyme activity. Cultures grown without catalase exhibited an absorption peak characteristic of peroxides. This absorption peak was removed by addition of catalase during or after growth. Oxygen was required for growth, but carbon dioxide was not produced. Malate and acetate stimulated growth at low concentrations. Glucose and thiosulfate were not oxidized, and cytochromes were not detectable by spectrophotometric analysis.